2011
DOI: 10.1021/jo102325s
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of 5-Methoxy-6-hydroxy-2-methylchromone-7-O- and 5-Hydroxy-2-methylchromone-7-O-rutinosides. Investigation of Their Cytotoxic Activities against Several Human Tumor Cell Lines

Abstract: The synthesis of two novel 2-methylchromone-7-O-rutinosides, whose synthetic precursors and themselves in vitro biological activities have been investigated based on the cytotoxcity against several human tumor cell lines, was reported. The synthesis features early-stage assembly of the acidic labile glycosidic bond between sugar and 2-methylchromone aglycon under a phase transfer catalyzed glycosidation condition, whereas all the other standard glycosylation conditions specific to a wide array of rutinosyl don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Flavonoids, a group of polyphenolic compounds that are abundant in plants, 590 include dietary components of potential importance to health. 591 In addition, flavanoids are emerging as a potentially significant unique group of pharmaceutical lead substrates.…”
Section: Applications Of Friedel–crafts In Total Synthesis Of Natural...mentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids, a group of polyphenolic compounds that are abundant in plants, 590 include dietary components of potential importance to health. 591 In addition, flavanoids are emerging as a potentially significant unique group of pharmaceutical lead substrates.…”
Section: Applications Of Friedel–crafts In Total Synthesis Of Natural...mentioning
confidence: 99%
“… 591 In addition, flavanoids are emerging as a potentially significant unique group of pharmaceutical lead substrates. 590 Among the several classes of flavonoids, dihydrochalcones exhibit a series of biologically remarkable activities, including antioxidant, 592,593 antiinflammatory, 594 antileishmanial, 595 antidiabetic, 596 anticancer 597 and molluscidal 598 properties. 599 Peng et al described the isolation and identification of a significant dihydrochalcone, named taccabulin E 633, from extracts of the plant species Tacca chantrieri and Tacca integrifolia .…”
Section: Applications Of Friedel–crafts In Total Synthesis Of Natural...mentioning
confidence: 99%
“…It was concluded that the problems observed with the two-stage glycosylation must occur after the bromination step. A number of literature examples of α-Fuc-(1–6)-GlcNAc synthesis highlight the extremely labile nature of the biologically important α-(1–6) linkage. , Kunz et al showed that the presence of arming groups such as benzyl protection on the fucose increase the instability of the α-(1–6) glycosidic bond . The highly reactive nature of the donor 7 , coupled with the sensitive glycosidic bond in the product 9 , was identified as the main reason for the low yields in the glycosylation reactions screened.…”
Section: Investigation Of Synthetic Applications Of Glycosyl Donorsmentioning
confidence: 99%
“…Flavonoids are a large family of polyphenolic compounds that represent dietary constituents of importance to good health as well as a potentially important new class of pharmaceutical lead substrates [1,2,3]. There are several subclasses of flavonoids, including aurones, chalcones, coumarins, flavones and isoflavones, which serve as the core structural units of numerous biologically active molecules [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%